1989
DOI: 10.1021/jm00124a011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of congeners and prodrugs. 3. Water-soluble prodrugs of taxol with potent antitumor activity

Abstract: Taxol has shown good in vivo antitumor activity in a number of test systems. The formulation of taxol for antitumor testing has been difficult. Esterification at either C-2' or C-7 resulted in loss of in vitro tubulin assembly activity but not cytotoxicity. These observations suggested that esters at C-2' and/or C-7, which would tend to promote water solubility, might serve as useful prodrugs of taxol. The reaction of taxol with either succinic anhydride or glutaric anhydride in pyridine solution at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(144 citation statements)
references
References 2 publications
(2 reference statements)
3
138
0
3
Order By: Relevance
“…PD0325901 analogue 7a was obtained in 68% yield (two steps) [15,18]. Derivation of the terminal amine group of 7awith succinic anhydride provided the hemisuccinate ester 8a in 85% yield [19]. The peptide conjugation reaction was initiated from the activation of 8a with PyBOP in the presence of DIPEA, followed by the addition of c(RGDyk) peptide, which afforded RGD-MEKI conjugate 9a in 45% yield.…”
Section: Scheme 1 Synthesis Of Compounds 5a-ementioning
confidence: 99%
See 1 more Smart Citation
“…PD0325901 analogue 7a was obtained in 68% yield (two steps) [15,18]. Derivation of the terminal amine group of 7awith succinic anhydride provided the hemisuccinate ester 8a in 85% yield [19]. The peptide conjugation reaction was initiated from the activation of 8a with PyBOP in the presence of DIPEA, followed by the addition of c(RGDyk) peptide, which afforded RGD-MEKI conjugate 9a in 45% yield.…”
Section: Scheme 1 Synthesis Of Compounds 5a-ementioning
confidence: 99%
“…Column chromatography was performed using 200-300 mesh silica with the proper solvent system according to TLC analysis using KMnO 4 stain and UV light to visualize the reaction components. Unless otherwise noted, 1 H-NMR (400 MHz), 19 F-NMR spectra (376 MHz) were recorded at ambient temperature using a BrukerAvance III400 MHz spectrometer (Bruker, Karlsruhecity, Germany). NMR data were reported as follows: chemical shift, multiplicity (s = singlet, d = doublet, t = triplet, m = multiplet and bs = broad singlet), coupling constant in Hz and integration.…”
Section: General Experimental Conditionsmentioning
confidence: 99%
“…It has been previously demonstrated that esterification at 2′-OH or 7-OH abolished the microtubule binding affinity of the conjugates but not the total toxicity. 28 The DX conjugates as ester prodrugs are expected to be cleaved to release free DX and exert their antitumor toxicity after cleavage. However, in the present 48 hours in vitro cytotoxicity study, the hydrolysis rate may not be fast enough to release all the DX.…”
mentioning
confidence: 99%
“…Prodrugs 3 and 4 were prepared starting by the reaction of the 2'-hydroxy function of PTX with 285 succinic anhydride according to the procedure of Deutsch (Deutsch et al, 1989). In order to facilitate the further PEGylation reaction, the carboxyl function of 2'-succinyl-paclitaxel was activated as N-hydroxysuccinimidil derivative (PTX-NHS, 2) using NHS and DCC.…”
Section: Chemistrymentioning
confidence: 99%